The multilateralization of policing: a case study of Rwanda before and after the 1994 genocide - Habarurema, Jean pierre (Centre for Law and Society, 2026)
Since the creation of the world, in every organised society, security matters have been given importance. In small local communities, communal security was controlled by the community members themselves. This structure helped in preventing and punishing crime at that level. However, smce the I 8th century, in Western countries, with urbanization and industrialization, crimes rate increased and reached a level that local policing was unable to control. 1 At this step, the state as the main regulator of security and order, created a centralised and organised police force, able to deal with violent crimes which were increasing day after day. 2 By doing so, the state wanted to monopolise policing but it did not realize its dream because the state police was unable to be omnipresent in all comers of the country where it was needed. As a result, for each time the state police was absent or far from the area where it was needed, the local population continued to find solutions to their security needs.3 Furthermore, since the 20th century, new ideas were developed that effective policing needs to be shared with the community for which security is kept. This philosophy, amongst other things, led to the restructuring of policing in many countries and the birth of 'community policing' as well as the birth and the development of private security companies and other non-state agencies engaged in providing security services. Some scholars argued that it was the era of the privatization of policing but Bayley and Shearing preferred to refer to what was occurring to policing as 'multilateralization'4 rather than 'privatization'. In this dissertation I rely on the works of these two scholars to discuss the issue of the 'multilateralization' of policing in the African context, in general, and in the Rwandan context, in particular. In the African context, before the colonization period, policing had always been carried out by community members. Indeed, community members had their own way of dealing with crime prevention and punishment. In addition, they had their own way of resolving disputes within families and small neighbourhoods.5 With colonization, although the colonizer wanted to enforce the law by use of the state police, this system of local policing remained operational, especially in rural areas.6 Moreover, even after colonization, nothing changed, as many states had no means to deal with security issues using only the state police whose human resources were limited. Furthermore, the philosophy of community policing which was developed in Western countries in 1990s, reached African countries but its implementation in Africa is different from its application in Western countries.7 Moreover, apart from the state police and the voluntary participation of the community in security matters, private security companies offering their services for money also burgeoned in many African countries. 8 This dissertation aims to discuss the issue of the 'multilateralization' of policing in general, with more emphasis on the Rwandan context, in particular. Different forms of policing which have taken place in Rwanda before and after the 1994 genocide will be discussed. The focus of the dissertation will thus be on the 'security governance'9 systems in place in Rwanda before and after the I 994 genocide. Also, an analysis will be made of the legal framework which has regulated the Rwandan policing during the above mentioned period. The social, legal and political implications of those forms of policing will also be discussed.